Massive gastric distension due to bulimia nervosa: a hotpot emergency. Issue 8 (16th August 2022) - Lee, Jordan D; Prabhakaran, Sowmya; Wilkie, Bruce D; Peng, Calvin; Thomson, Benjamin N J
Abstract: Acute massive gastric distension is a rare but potentially life-threatening surgical complication of bulimia nervosa. This results from repeated binge eating and is likely compounded by increased gastric compliance and delayed gastric emptying. We describe a case of acute massive gastric distension in a 26-year-old female with undiagnosed bulimia nervosa who underwent a laparotomy and anterior gastrotomy after failed conservative measures for gastric decompression. It highlights the importance of early recognition of a potentially life-threatening condition and that a multi-disciplinary approach is necessary to prevent the recurrence and morbidity associated with it.